High Protein Milk Intervention in Malnourished Children and Its Effect on Weight Gain and Renal Function - Kusharto, Clara Meliyanti; Ekawidyani, Karina Rahmadia; Tanziha, Ikeu; Setiawan, Budi; Rosmiati, Risti; Irawan, Andi Muh Asrul (Jurnal Gizi dan Pangan, 2019)
This study aimed to determine the effect of high-protein milk intervention on weight gain and renal function in malnourished children. This research is a randomized controlled trial (RCT). A total of 52 wasting children (BAZ -3<SD<-2) aged 3-12 years were selected by simple random sampling from five primary schools (6-12 years) and two Community Health Center (children below 6 years). Subjects were divided into two groups; control group (26) and intervention group (26). The intervention group was given high-protein milk (HPM) 3x25 g each day for 12 weeks. Body weight, serum creatinine, and urea were measured at week 0 (baseline), 6th (midline), and 12th (endline). The study showed that the body weight of the intervention group significantly increased by 1.54 kg after 12 weeks of high-protein milk consumption. Serum urea and creatinine levels in the intervention group also significantly increased (p<0.05). The increase in serum urea and creatinine levels in the intervention group were still within the normal range (normal serum urea level 15-43 mg/dl and normal creatinine level 0.6-1.2 mg/dl). This suggests that significant increases in urea and creatinine levels of the intervention group were normal because of increased protein intake and body muscle mass and it did not lead to renal function abnormalities.